Neural Tissue Homeostasis and Repair Is Regulated via CS and DS Proteoglycan Motifs. - Hayes, A.J.; Melrose, J. (Frontiers in cell and developmental biology, 2021)
Chondroitin sulfate (CS) is the most abundant and widely distributed glycosaminoglycan (GAG) in the human body. As a component of proteoglycans (PGs) it has numerous roles in matrix stabilization and cellular regulation. This chapter highlights the roles of CS and CS-PGs in the central and peripheral nervous systems (CNS/PNS). CS has specific cell regulatory roles that control tissue function and homeostasis. The CNS/PNS contains a diverse range of CS-PGs which direct the development of embryonic neural axonal networks, and the responses of neural cell populations in mature tissues to traumatic injury. Following brain trauma and spinal cord injury, a stabilizing CS-PG-rich scar tissue is laid down at the defect site to protect neural tissues, which are amongst the softest tissues of the human body. Unfortunately, the CS concentrated in gliotic scars also inhibits neural outgrowth and functional recovery. CS has well known inhibitory properties over neural behavior, and animal models of CNS/PNS injury have demonstrated that selective degradation of CS using chondroitinase improves neuronal functional recovery. CS-PGs are present diffusely in the CNS but also form denser regions of extracellular matrix termed perineuronal nets which surround neurons. Hyaluronan is immobilized in hyalectan CS-PG aggregates in these perineural structures, which provide neural protection, synapse, and neural plasticity, and have roles in memory and cognitive learning. Despite the generally inhibitory cues delivered by CS-A and CS-C, some CS-PGs containing highly charged CS disaccharides (CS-D, CS-E) or dermatan sulfate (DS) disaccharides that promote neural outgrowth and functional recovery. CS/DS thus has varied cell regulatory properties and structural ECM supportive roles in the CNS/PNS depending on the glycoform present and its location in tissue niches and specific cellular contexts. Studies on the fruit fly, Drosophila melanogaster and the nematode Caenorhabditis elegans have provided insightful information on neural interconnectivity and the role of the ECM and its PGs in neural development and in tissue morphogenesis in a whole organism environment.